2020
DOI: 10.1109/access.2020.2997727
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive and Flexible Brain Energized Full Body Exoskeleton With IoT Edge for Assisting the Paralyzed Patients

Abstract: The paralyzed population is increasing worldwide due to stroke, spinal code injury, post-polio, and other related diseases. Different assistive technologies are used to improve the physical and mental health of the affected patients. Exoskeletons have emerged as one of the most promising technology to provide movement and rehabilitation for the paralyzed. But exoskeletons are limited by the constraints of weight, flexibility, and adaptability. To resolve these issues, we propose an adaptive and flexible Brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…6 illustrates a few major optimization tasks in the domain of HEMS. Jacob et al (2020) presented a "fuzzy TOPSIS decision-making" mechanism following a real-time pricing scheme to shift appliances efficiently. The proposed system, "fuzzy TOPSIS decision-making", gives an assessment of power consumption of multiple power users and directs for optimum energy distribution.…”
Section: Role Of Optimization Techniques In Hemssmentioning
confidence: 99%
“…6 illustrates a few major optimization tasks in the domain of HEMS. Jacob et al (2020) presented a "fuzzy TOPSIS decision-making" mechanism following a real-time pricing scheme to shift appliances efficiently. The proposed system, "fuzzy TOPSIS decision-making", gives an assessment of power consumption of multiple power users and directs for optimum energy distribution.…”
Section: Role Of Optimization Techniques In Hemssmentioning
confidence: 99%
“…In a study of IoT-Based Medication Box, researchers have demonstrated a successful prototype design of medication management system powered by drone [59]. Also Jacob, et al (2020) supports the paralyzed patients with brain energized full body Exoskeleton with IoT edge design [60]. Thus, under the proper handling of challenges of the utilization of sensors, the independent elderly would be benefited by reducing the costs in their healthcare and improvement on life quality [35].…”
Section: Low User-experiencementioning
confidence: 99%
“…This study describes a single use case to show perspectives for the use of robots in nursing care. Additionally, IoT developments have been implemented to support e-Health processes to vulnerable people and persons with physical disabilities [6,7].…”
Section: Introductionmentioning
confidence: 99%